High-valence metal organic salt and metal inorganic compound composite electrolyte additive, electrolyte containing additive and application
By using a composite electrolyte additive of high-valent metal organic salts and inorganic halides/oxygen compounds, the problem of unstable electrode/electrolyte interface in metal-based secondary batteries is solved, the battery cycle life is extended and the safety is improved, and it is suitable for a variety of battery systems.
Patent Information
- Application Number
- CN202510929859.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2025-09-26
AI Technical Summary
Existing electrolyte systems in metal-based secondary batteries have problems such as unstable electrode/electrolyte interface and increased side reactions under high voltage, which leads to a decrease in battery cycle life and safety hazards.
By using a composite electrolyte additive of high-valent metal organic salts and metal inorganic compounds, the electrode/electrolyte interface layer is repaired during the charge and discharge process through the synergistic effect of high-valent metal cations and inorganic halides/oxygen compounds, forming a high ion conductivity, low impedance composite film, thereby inhibiting electrolyte side reactions and electrode structure degradation.
It significantly extends the battery cycle life, inhibits dendrite growth, and improves the stability of positive electrode materials. It is suitable for a variety of metal negative electrodes and high-voltage positive electrodes, and is compatible with a variety of solvents and mainstream lithium salts to meet the multi-scenario needs of power batteries and energy storage batteries.
Smart Images

Figure CN120709500A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composite electrolyte additive of a high-valent metal organic salt and a metal inorganic compound, an electrolyte containing the additive and applications thereof, belonging to the technical field of battery materials. Background Art
[0002] As the global energy structure transformation accelerates, the development of energy storage systems with both high energy density and cost-effectiveness has become a core issue of the energy revolution. Metal-based batteries are considered to be the next generation energy storage system with the greatest industrial potential due to their breakthrough theoretical energy density. However, metal-based secondary batteries place higher demands on electrolyte performance. Traditional electrolyte systems often suffer from problems such as unstable electrode / electrolyte interface and increased side reactions under high voltage, which lead to battery cycle life degradation and safety hazards. Existing additive technologies mostly focus on single function optimization. For example, fluorine-containing organic salts can improve ionic conductivity, but they are prone to cause corrosion of aluminum current collectors; although inorganic halides can passivate the electrode surface, they have defects such as poor thermal stability and easy hydrolysis. In recent years, organic metal salts have attracted attention due to their tunable redox properties and coordination ability, but their high-valent metal centers (such as Fe 3+ 、Co 3+ ) is prone to disproportionation reaction in conventional solvents, resulting in insufficient stability. Based on this, the technical solution is based on organic metal salts as electrolyte additives. It is very meaningful to develop a composite additive that can simultaneously improve the above-mentioned technical problems. Summary of the Invention
[0003] To address issues such as unstable electrode / electrolyte interfaces and increased decomposition side reactions at high voltages in existing electrolyte systems, the present invention discloses a composite electrolyte additive comprising a high-valent metal organic salt and a metal inorganic compound. In this system, the anions in the high-valent metal organic salt can undergo self-polymerization or electrochemical polymerization, while the high-valent metal cations are oxidizing, promoting self-polymerization or electrochemical polymerization of organic anions and / or electrolyte solvents. These additives can then be reduced by a metal negative electrode with strong reducing power, or undergo chemical replacement reactions with inorganic halides / oxygen compounds, thereby simultaneously optimizing the interfaces between the positive and negative electrodes of metal batteries and providing a novel regulatory strategy for high-stability interface engineering in metal-based secondary batteries.
[0004] The specific technical solutions of the present invention are:
[0005] 1. A composite electrolyte additive of a high-valent metal organic salt and a metal inorganic compound, wherein the high-valent metal organic salt is an organic metal salt composed of a high-valent metal cation and a polymerizable organic anion, and the metal inorganic compound is at least one of a metal halide or a metal oxide.
[0006] Preferably, the high-valent metal organic salt is iron (III) p-toluenesulfonate (Fe(OTs) 3 ), cerium (IV) acrylate (Ce(CH2=CHCOO)4), ruthenium (III) styrene sulfonate (Ru(SSA)3), cobalt (III) thiophene carboxylate (Co(ThCOO)3), manganese (III) aniline sulfonate (Mn(AS)3), vanadium (V) pyrrolidine sulfonate (V(PyS)5), copper (II) acrylate-o-phenanthroline complex (Cu(phen) 22 ), silver (I) acetylide (AgC≡CR) or at least one or more thereof.
[0007] Preferably, the metal halide is at least one of ZnCl2, ZnI2, MgBr2, AlCl3, SnCl2, FeCl3, and CuBr2, and the metal oxide is one or more of MgO, ZnO, ZnS2, MgS2, Al2S3, SnS2, Fe2Se3, and CuSe2.
[0008] Preferably, the molar ratio of the high-valent metal organic salt to the metal inorganic compound is 1:0.1-1:5.
[0009] 2. An electrolyte, which comprises, by mass fraction, 0.01%-15% of a composite electrolyte additive; 5%-30% of an electrolyte salt; 60%-90% of a solvent; and 0.01%-10% of other additives.
[0010] Preferably, the solvent is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, ethyl acetate, water, and methanol.
[0011] Preferably, the electrolyte salt is selected from at least one of lithium hexafluorophosphate, lithium bisfluorosulfonyl imide, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, sodium hexafluorophosphate, sodium bisfluorosulfonyl imide, sodium bis(trifluoromethanesulfonyl)imide, sodium perchlorate, potassium hexafluorophosphate, potassium bisfluorosulfonyl imide, potassium bis(trifluoromethanesulfonyl)imide, potassium perchlorate, potassium hydroxide, sodium hydroxide, zinc sulfate, and sodium sulfate.
[0012] Preferably, the other additives are selected from at least one of vinylene carbonate, fluoroethylene carbonate, lithium difluorophosphate, 1,3-propane sultone, vinyl sulfate, ethylene glycol, urea, glucose, polyethylene glycol, and sorbitol.
[0013] 3. Application of the electrolyte in metal-based secondary batteries.
[0014] The beneficial effects of the present invention are:
[0015] The electrolyte additive disclosed in the present invention is a composite additive formed by an organic salt rich in high-valent metal cations and a metal halide / oxygen compound, which has the following advantages: (1) By introducing the synergistic effect of high-valent metal organic salts and inorganic halides / oxygen compounds, the defects of the electrode / electrolyte interface layer (CEI / SEI) are continuously repaired during the charge and discharge process. High-valent metal cations (such as Fe 3+ 、Ce 4+ 、Ru 3+ The strong oxidizing property of inorganic halides (such as acrylate, styrene sulfonate, etc.) can trigger the self-polymerization or electrochemical polymerization of organic anions (such as acrylate, styrene sulfonate, etc.), and combine with high-valent metal cations to replace the metals in inorganic halides (such as Zn, Mg, etc.), and synergistically construct a high ion conductivity, low impedance composite CEI membrane, improve the stability of positive electrode materials (such as high nickel ternary, lithium-rich manganese-based, etc.), effectively inhibit the side reaction of the electrolyte and the degradation of the electrode structure, and significantly extend the battery cycle life; (2) Inorganic halides / oxygen compounds (such as ZnCl2, AlCl3, etc.) induce the formation of metal sulfide, halide-rich halides on the surface of the metal negative electrode (lithium / sodium / potassium). The composite SEI film of the compound inhibits dendrite growth and reduces interfacial impedance. At the same time, the high-valent metal cations are reduced to further enhance the mechanical strength of the SEI; (3) The additive is suitable for metal negative electrodes such as lithium, sodium, potassium, and zinc, and is also suitable for high-voltage positive electrodes (such as lithium cobalt oxide, lithium nickel manganese oxide) and sulfur-based positive electrodes. The electrolyte system supports a variety of solvents such as carbonates and ethers (such as EC, DMC, EMC), and is compatible with mainstream lithium salts / sodium salts (LiPF6, NaClO4, KFSI) and other additives (such as VC, FEC, LiDFP), meeting the needs of multiple scenarios such as power batteries and energy storage batteries.
[0016] Other advantages, objects, and features of the present invention will be described in part in the following description and, in part, will be apparent to those skilled in the art upon examination of the following description or may be learned from practice of the present invention. The objects and other advantages of the present invention may be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below with reference to the accompanying drawings, in which:
[0018] Figure 1 This is a graph showing the cycling performance test of the electrolyte in Example 1 applied to a Li-Li symmetric battery;
[0019] Figure 2 This is a graph showing the cycling performance test of the electrolyte of Example 2 applied to a Na-Na symmetric battery;
[0020] Figure 3A comparison of the surface morphologies of the sodium metal negative electrodes of the electrolyte batteries prepared in Example 3 and Comparative Example 3 after cycling;
[0021] Figure 4 A comparison chart of the cycle performance of batteries assembled with the electrolytes prepared in Example 4 and Comparative Example 4;
[0022] Figure 5 A comparison chart of the cycle performance of batteries assembled using the electrolytes prepared in Example 5 and Comparative Example 5;
[0023] Figure 6 The figure is a comparison of the cycle performance of batteries assembled with the electrolytes prepared in Example 6 and Comparative Example 6. DETAILED DESCRIPTION
[0024] The following describes the embodiments of the present invention by means of specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present invention, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0025] Example 1
[0026] An electrolyte, comprising the following components by mass fraction:
[0027] (1) Conventional electrolyte formula
[0028] Solvent: Ethylene carbonate (EC): ethyl methyl carbonate (EMC) mass ratio is 3:7, accounting for 85% of the total mass of the electrolyte;
[0029] Salt: lithium bis(fluorosulfonyl)imide (LiFSI), accounting for 12% of the total mass of the electrolyte;
[0030] (2) Composite additive composition
[0031] The molar ratio of cerium (IV) acrylate (Ce(CH3=CHCOO)4) to ZnI2 is 1:1, accounting for 1% of the total mass of the electrolyte;
[0032] (3) Other additives: Fluoroethylene carbonate (FEC), accounting for 2% of the total mass of the electrolyte
[0033] The electrolyte prepared in Example 1 was applied to a metal symmetrical battery, such as Figure 1 As shown, the symmetrical battery cycled in the electrolyte with the composite additives is -2and 1mAh cm -2 Under normal conditions, it can be stably cycled for more than 500 hours with an overpotential of only 8mV. The ratio of metallic lithium to NCM811 is such that the capacity retention rate is 92% after 500 cycles. The positive electrode CEI film contains Ce-O-Zn inorganic compounds and an organic polymer layer, while the negative electrode SEI film contains ZnS / ZnF2 / ZnI2, which inhibits the growth of lithium dendrites.
[0034] Example 2
[0035] An electrolyte, comprising the following components by mass fraction:
[0036] (1) Conventional electrolyte formula
[0037] Solvent: propylene carbonate (PC): ethyl acetate (EA) mass ratio 1:1, accounting for 85% of the total mass of the electrolyte;
[0038] Salt: sodium hexafluorophosphate (NaPF6), accounting for 10% of the total mass of the electrolyte;
[0039] (2) Composite additive composition
[0040] The molar ratio of iron (III) p-toluenesulfonate (Fe(OTs)3 to SnBr2 is 1:3, accounting for 5% of the total mass of the electrolyte;
[0041] (3) Other additives: None
[0042] The electrolyte prepared in Example 2 was applied to a Na-Na symmetrical battery. Figure 2 The symmetrical battery cycled in the electrolyte with the composite additives at 1 mA cm -2 and 1 mA h cm -2 Under the condition of low voltage, it can cycle stably for more than 500 hours with an overpotential of only 50-70mV.
[0043] Example 3
[0044] An electrolyte, comprising the following components by mass fraction:
[0045] (1) Conventional electrolyte formula
[0046] Solvent: γ-butyrolactone (GBL), accounting for 85% of the total mass of the electrolyte;
[0047] Salt: potassium bis(trifluoromethanesulfonyl)imide (KTFSI), accounting for 10% of the total mass of the electrolyte;
[0048] (2) Composite additive composition
[0049] The molar ratio of vanadium (V) pyrrole sulfonate (V(PyS)5 to MgF2 is 1:5, accounting for 3% of the total mass of the electrolyte;
[0050] (3) Other additives: ethyl sulfite, accounting for 2% of the total mass of the electrolyte.
[0051] Comparative Example 3
[0052] An electrolyte, comprising the following components by mass fraction:
[0053] (1) Conventional electrolyte formula
[0054] Solvent: γ-butyrolactone (GBL), accounting for 88% of the total mass of the electrolyte;
[0055] Salt: potassium bis(trifluoromethanesulfonyl)imide (KTFSI), accounting for 10% of the total mass of the electrolyte;
[0056] (2) Other additives: ethyl sulfite, accounting for 2% of the total mass of the electrolyte.
[0057] The electrolytes prepared in Example 3 and Comparative Example 3 were respectively applied to secondary batteries, with potassium metal as the negative electrode and Prussian blue analogs (PBAs) as the positive electrode, and the batteries were subjected to cycle tests. Figure 3 This is a comparison chart of the surface test results of the metal negative electrode after cycling of the electrolyte batteries prepared in Example 3 and Comparative Example 3; the surface of the potassium metal negative electrode obtained by disassembly after cycling is covered with a dense and uniform SEI film, while the surface of the potassium metal after cycling in the electrolyte without additives presents an uneven structure with more dendrites and pore structures.
[0058] Example 4
[0059] An electrolyte, comprising the following components by mass fraction:
[0060] (1) Conventional electrolyte formula
[0061] Solvent: water + ethylene glycol, volume ratio 1:1, accounting for 90% of the total mass of the electrolyte;
[0062] Salt: zinc trifluoromethanesulfonate Zn(CF3SO3)2, accounting for 4% of the total mass of the electrolyte;
[0063] (2) Composite additive composition
[0064] The molar ratio of cobalt (III) thiophene carboxylate (Co(ThCOO)3) to FeCl3 is 1:2, accounting for 6% of the total mass of the electrolyte;
[0065] (3) Other additives: None
[0066] Comparative Example 4
[0067] An electrolyte, comprising the following components by mass fraction:
[0068] Solvent: water + ethylene glycol, volume ratio 1:1, accounting for 96% of the total mass of the electrolyte;
[0069] Salt: zinc trifluoromethanesulfonate Zn(CF3SO3)2, accounting for 4% of the total mass of the electrolyte.
[0070] The electrolytes prepared in Example 4 and Comparative Example 4 were respectively applied to secondary batteries, with metal zinc as the negative electrode and MnO2 as the positive electrode, and the batteries were subjected to cycle tests. Figure 4 The comparison chart of the electrolyte battery prepared in Example 4 and Comparative Example 4 after cycling is shown in Figure 3A g. -1 The capacity retention rate after 1300 cycles is higher than that of comparative example 4 without additives.
[0071] Example 5
[0072] An electrolyte, comprising the following components by mass fraction:
[0073] (1) Conventional electrolyte formula
[0074] Solvent: 1,3-dioxolane (DOL): ethylene glycol dimethyl ether (DME) mass ratio 1:1, accounting for 80% of the total mass of the electrolyte;
[0075] Salt: LiTFSI, accounting for 10% of the total mass of the electrolyte;
[0076] (2) Composite additive composition
[0077] The molar ratio of ruthenium (III) styrene sulfonate (Ru(SSA)3, 3% by mass) to CuBr2 is 1:0.5, accounting for 4.5% of the total mass of the electrolyte;
[0078] (3) Other additives: LiNO3, accounting for 5.5% of the total mass of the electrolyte.
[0079] Comparative Example 5
[0080] An electrolyte, comprising the following components by mass fraction:
[0081] (1) Conventional electrolyte formula
[0082] Solvent: 1,3-dioxolane (DOL): ethylene glycol dimethyl ether (DME) mass ratio 1:1, accounting for 84.5% of the total mass of the electrolyte;
[0083] Salt: LiTFSI, accounting for 10% of the total mass of the electrolyte;
[0084] (2) Other additives: LiNO3, accounting for 5.5% of the total mass of the electrolyte.
[0085] The electrolytes prepared in Example 5 and Comparative Example 5 were respectively applied to secondary batteries, with metallic lithium as the negative electrode and a mixture of sulfur and carbon materials as the positive electrode. Figure 5 The comparison diagram of the electrical performance test of the battery using the electrolyte prepared in Example 5 and Comparative Example 5 is shown in FIG. Figure 5 As shown in a, the battery using the electrolyte prepared in Example 5 can achieve a current density of nearly 1200 mA hg at a current density of 0.1C. -1 The reversible specific capacity of Comparative Example 5 is less than 800 mAh g -1 .like Figure 5 As shown in Figure b, the battery using the electrolyte prepared in Example 5 still maintains a capacity of 423.5 mAh g after 700 cycles at 0.5C. -1 , while the reversible specific capacity of comparative example 5 is only 165.9 mAh g -1 , indicating that the use of composite additives can improve the cycle performance of the whole battery.
[0086] Example 6
[0087] A solid electrolyte, comprising the following components by mass:
[0088] (1) Solid electrolyte formula
[0089] PEO-LiTFSI, accounting for 95% of the total mass;
[0090] (2) Composite additive composition
[0091] The molar ratio of silver (I) acetylide (AgC≡CR, mass fraction 0.3%) to MgBr2 is 1:2, accounting for 5% of the total mass;
[0092] (3) Other additives: None.
[0093] Comparative Example 6
[0094] A solid electrolyte, comprising the following components by mass:
[0095] Solid electrolyte formula: PEO-LiTFSI, accounting for 100% of the total mass.
[0096] The electrolytes prepared in Example 6 and Comparative Example 6 were respectively applied to secondary batteries, with metallic lithium as the negative electrode and a mixture of sulfur and carbon materials as the positive electrode. The lithium metal and sulfur / carbon composite materials were matched with the above solid electrolytes, and the sulfur loading was 5 mg / cm 2 When the capacity is maintained at 92% after 50 cycles (compared with the capacity after stabilization), the capacity maintenance rate of the control sample without adding composite additives is only 60% after 50 cycles.
[0097] The above examples and comparative examples illustrate that the present invention introduces organic salts with high-valent metal cations and inorganic halides / oxygen compounds simultaneously into conventional electrolytes, enabling dynamic repair of defects in the electrode / electrolyte interface layer. The anions in the high-valent metal organic salts are organic ions capable of self-polymerization or electrochemical polymerization. The high-valent metal cations have strong oxidizing properties, promoting self-polymerization or electrochemical polymerization of organic anions and / or electrolyte solvents, and can be reduced by metal negative electrodes with strong reducing power. The composite electrolyte additive significantly enhances the electrochemical performance of secondary batteries.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not limiting. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions, which should all be included in the scope of the claims of the present invention.
Claims
1. A composite electrolyte additive of a high-valent metal organic salt and a metal inorganic compound, characterized in that: The high-valent metal organic salt is an organic metal salt composed of a high-valent metal cation and a polymerizable organic anion, and the metal inorganic compound is at least one of a metal halide or a metal oxide.
2. The high-valent metal organic salt and metal inorganic compound composite electrolyte additive according to claim 1, characterized in that: The high-valent metal organic salt is iron (III) p-toluenesulfonate (Fe(OTs) 3 ), cerium (IV) acrylate (Ce(CH2=CHCOO)4), ruthenium (III) styrene sulfonate (Ru(SSA)3), cobalt (III) thiophene carboxylate (Co(ThCOO)3), manganese (III) aniline sulfonate (Mn(AS)3), vanadium (V) pyrrolidine sulfonate (V(PyS)5), copper (II) acrylate-o-phenanthroline complex (Cu(phen) 22 ), silver (I) acetylide (AgC≡CR) or at least one or more thereof.
3. The high-valent metal organic salt and metal inorganic compound composite electrolyte additive according to claim 1, characterized in that: The metal halide is at least one of ZnCl2, ZnI2, MgBr2, AlCl3, SnCl2, FeCl3, and CuBr2, and the metal oxide is one or more of MgO, ZnO, ZnS2, MgS2, Al2S3, SnS2, Fe2Se3, and CuSe2.
4. The high-valent metal organic salt and metal inorganic compound composite electrolyte additive according to claim 1, characterized in that: The molar ratio of the high-valent metal organic salt to the metal inorganic compound is 1:0.1-1:
5.
5. An electrolyte, characterized in that Calculated by mass fraction, the electrolyte comprises 0.01%-15% of a composite electrolyte additive; 5%-30% of an electrolyte salt; 60%-90% of a solvent; and 0.01%-10% of other additives.
6. The electrolyte according to claim 5, characterized in that The solvent is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, ethyl acetate, water, and methanol.
7. The electrolyte according to claim 5, characterized in that The electrolyte salt is selected from at least one of lithium hexafluorophosphate, lithium bisfluorosulfonyl imide, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, sodium hexafluorophosphate, sodium bisfluorosulfonyl imide, sodium bis(trifluoromethanesulfonyl)imide, sodium perchlorate, potassium hexafluorophosphate, potassium bisfluorosulfonyl imide, potassium bis(trifluoromethanesulfonyl)imide, potassium perchlorate, potassium hydroxide, sodium hydroxide, zinc sulfate, and sodium sulfate.
8. The electrolyte according to claim 5, characterized in that The other additives are selected from at least one of vinylene carbonate, fluoroethylene carbonate, lithium difluorophosphate, 1,3-propane sultone, vinyl sulfate, ethylene glycol, urea, glucose, polyethylene glycol, and sorbitol.
9. Application of the electrolyte in metal-based secondary batteries.
